Controle social na política de financiamento da educação: uma análise da atuação do conselho do FUNDEB no município de Imperatriz/MA - ALVES, Siloah Jesseni Gomes (2022)
This thesis had as object of study the procedure of the Fundeb Council of Imperatriz/MA as a guaranteeing instrument of social control of education resources. It was intended to answer the problem: How does the Fundeb Council of Imperatriz/MA act in relation to the social control it exerts over the spent of public resources for financing basic education? A qualitative approach with the choice of a critical theory of reality, analyzing the performance of the Council in relation to the social control it exerts over public spending on the financing of basic education. In theory, the operation of the Council should contribute to the consolidation of social control over the financing of public basic education. To verify this performance, bibliographic research and document analysis was used, having as main instrument for data collection the minutes of Council meetings. The research results show that in the Fundeb Board of Imperatriz there are problems of ineffective participation. We identified as obstacles to the exercise of social control: the lack of training, inferred from the few training records for the counselors; variation in the frequency of Conseil meetings and in the presence of members; mismatch of information and absence of answers regarding the requested clarifications; and lack of dialogue and in-depth discussions about the documents analyzed and the topics addressed in the meetings. In general, despite the predisposition and the effort of the members of the Council of Imperatriz, evidenced by the presence in the meetings, questions raised and reservations made, the actions of the councilors proved to be empty of autonomy and effective participation. In that regard, we found that although the spaces for participation in the supervision of public funds for education have been extended at the municipal level, the effectiveness has been compromised. The technical product of the research consists of an action plan with suggestions, strategies and notes made from the deficiencies identified in the results.